Genetic Evidence for the Association between Schizophrenia and Breast Cancer. Issue 4 (2018) - Shi, Jiajun; Shu, Xiang; Wu, Lang; Cai, Qiuyin; Long, Jirong; Zheng, Wei; Chang-Claude, Jenny; Shen, Chen-Yang; Wen, Wanqing; Brenner, Hermann; Wu, Pei-Ei; Wang, Shuyang; et al.
No abstract available